In vitro cytotoxicity evaluation of thioureaderivatives bearing Salix sp. constituent againstHK-1 cell lines - Norsyafikah Asyilla, Nordin; Vannessa, Lawai; Zainab, Ngaini; Ainaa Nadiah, Abd Halim; Siaw, San Hwang; Reagan, Entigu Linton; Boon, Kiat Lee; Paul Matthew, Neilsen (Taylor & Francis Group, 2020)
In searching for drugs from natural product scaffolds has gained inter-est among researchers. In this study, a series of twelve halogenatedthiourea (ATX 1-12)viachemical modification of aspirin (a naturalproduct derivative) and evaluated for cytotoxic activity against naso-pharyngeal carcinoma (NPC) cell lines, HK-1 via MTS-based colorimetricassay. The cytotoxicity studies demonstrated that halogens atmetapos-ition ofATXshowed promising activity against HK-1 cells (IC50value15mM) in comparison to cisplatin, a positive cytotoxic drug (IC50value¼8.9 ± 1.9mM).ATX 11, bearing iodine atmetaposition, showed robustcytotoxicity against HK-1 cells with an IC50value of 4.7 ± 0.7mM.Molecular docking interactions betweenATX 11and cyclooxygenase-2demonstrated a robust binding affinity value of8.1 kcal/mol as com-pared to aspirin’sbindingaffinityvalueof6.4 kcal/mol. The findingsrepresent a promising lead molecule from natural product with excel-lent cytotoxic activity against NPC cell lines.